Comparative Analysis of COVID-19 Pandemic-Related Mental Health Effects on Children with Household Healthcare Workers vs. Those Without - Vallabhaneni, Rohil (International Journal of Psychology, 2024)
Purpose: The primary objective of this pilot study is to investigate and comprehend the impact of the COVID-19 pandemic on children's mental health based on the presence of household members working in healthcare settings. Methods: Permission was secured from the Research Department of a densely populated county in the state of Georgia. Subsequently, an online survey was conducted among participants consisting of high school and middle school students, aiming to evaluate their mental health experiences three years following the onset of the pandemic in the United States. The survey included questions related to fear, sadness, preferences for online schooling, changes in sleeping habits, and whether anyone in the household worked in a healthcare setting. Responses were collected on a Likert scale with options "Yes," "No," and "Maybe." Findings: Among both groups of children about two thirds reported no increase in fear three years after the onset of pandemic. Around 25% of the children in both groups reported increased sadness. The majority of children in either group did not prefer online schooling. Unique Contribution to Theory, Practice and Policy: This survey underscores the need to consider household dynamics, specifically the presence of healthcare workers, when addressing children's sleeping habits during global stress situations such as pandemics.